Analysis of the Role of Facilitators in Waste Management in Pekanbaru City - Willya Achmad (Jurnal Restorasi : Hukum dan Politik, 2024)
Mentoring is an effort to involve the community in developing their various potentials so that they are able to achieve a better quality of life. The 3R waste management mentoring activity in Pekanbaru City was carried out to facilitate the community in the decision-making process in 3R waste management in their environment. In the implementation of this mentoring program, it is necessary to have qualified human resources (HR) capable of acting as facilitators, communicators and dynamists during the program. A companion is a key actor in developing the community so that the community is able to overcome the waste problem in their environment. The 3R waste management assistance in Pekanbaru City was carried out for two years. The results of the monitoring and evaluation that have been carried out are still not optimal. Mentoring can be said to be successful if the results of the mentoring are able to develop mindsets, attitudes and patterns of action in the community they are assisting. Follow-up actions taken by facilitators in optimizing community participation in 3R waste management are establishing KOMPAS (Waste Management Community), waste banks, socialization to relevant agencies, and testing organic rice using compost that has been produced.